2003
DOI: 10.1046/j.1523-1747.2003.12540.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Ferritin is Associated With Alopecia in Women

Abstract: Alopecia in women is a common problem, and conflicting observational data have failed to determine whether an association exists between alopecia and iron deficiency in women. We therefore utilized an analytical cross-sectional methodology to evaluate whether common types of alopecia in women are associated with decreased tissue iron stores, as measured by serum ferritin. We studied patients with telogen effluvium (n = 30), androgenetic alopecia (n = 52), alopecia areata (n = 17), and alopecia areata totalis/u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
128
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 39 publications
12
128
3
7
Order By: Relevance
“…Maximum number was found in the age group of 21-30 years in both groups. 9 Also not similar to a cross sectional study by Amade Bregy and Ralph Trueb of total 181 females, where mean age of 22 tellogen effluvium patients was 39.23 years(range,13-60). 5 Data showed that highest percentage patients with telogen effluvium were in the age group 21 to 30 years (50.0%) .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Maximum number was found in the age group of 21-30 years in both groups. 9 Also not similar to a cross sectional study by Amade Bregy and Ralph Trueb of total 181 females, where mean age of 22 tellogen effluvium patients was 39.23 years(range,13-60). 5 Data showed that highest percentage patients with telogen effluvium were in the age group 21 to 30 years (50.0%) .…”
Section: Resultsmentioning
confidence: 64%
“…They found that the mean ferritin level were significantly lower in androgenic alopecia and alopecia areata but not in telogen effluvium and alopecia areata totalis/universalis. 9 In a cross sectional study of a total 181 female, 22 was with telogen effluvium and 159 were female pattern hair loss. The mean serum ferritin level was 40.09 ìgm/l (range 2-209).…”
Section: Resultsmentioning
confidence: 99%
“…iron deficiency leads to certain kinds of hair loss e.g. female pattern hair loss, telogen effluvium, alopecia areata, alopecia universal [12][13][14][15][16][17], however some researchers denied such claims [18][19][20][21][22]. Clinically iron deficiency is defined either as an increase in total iron binding capacity tion of ferritin under 40 ng/mL [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the studies by Rushton and Kantor et al showing a statistically significant decrease in serum hemoglobin and serum ferritin levels in patients with CTE. 3,4 Similarly, Obaidat et al have reported a significant association between serum ferritin levels and CTE, in their study on potential relation between TE and Iron deficiency in women. 2 On the other hand, there are also studies where anemia of iron deficiency does not seem to play a role in manifestation of CTE.…”
Section: Discussionmentioning
confidence: 88%
“…Studies by Obaidat, Rushton, and Kantor et al, have shown a statistically significant decrease in serum hemoglobin and serum ferritin levels in CTE patients, and a significant improvement in hair loss after supplementing with iron in these patients. [2][3][4] The only drawback of the study was the small number of patients which may not reflect the true picture. There are mixed and conflicting results regarding the high prevalence of thyroid levels as a causing of CTE.…”
Section: Introductionmentioning
confidence: 99%